2018
DOI: 10.1016/j.nefro.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D level is negatively associated with serum phosphorus level among stage 3a-5 chronic kidney disease patients

Abstract: Serum P is likely to have a direct negative impact on serum 25(OH)D. Further studies are needed to determine the underlying mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In CKD patients with impaired renal phosphate excretion, both 25 (OH)D and 1,25 (OH) 2 D should have positive association with serum phosphorus. The negative association observed in previous studies (12,38) and confirmed in the current study raises many possible mechanisms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In CKD patients with impaired renal phosphate excretion, both 25 (OH)D and 1,25 (OH) 2 D should have positive association with serum phosphorus. The negative association observed in previous studies (12,38) and confirmed in the current study raises many possible mechanisms.…”
Section: Discussionsupporting
confidence: 83%
“…Increased FGF23 level triggered by increased serum P might inhibit 25 hydroxylase or stimulate 24 hydroxylase. FGF23 negatively correlates with 25 OH D in mice, however, similar relation in human CKD patients was not encountered [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Desjardins et al. found that FGF23 increased with decreasing kidney function [ 23 , 24 ], while 25(OH)D3 levels decreased with increasing CKD stage in predialysis patients [ 25 , 26 ]. Consistent with these findings, serum 25(OH)D3 levels were negatively correlated with kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the relationship between FGF23 and CAC is unstable. For the association between 25(OH)D3 and CAC, several studies have shown that low levels of 25(OH)D3 are linked to greater arterial calcification scores [ 25 ] and that patients with higher calcification scores have lower levels of 25(OH)D3 [ 26 ]. However, the study of Pillar et al.…”
Section: Discussionmentioning
confidence: 99%